Refining the System of Local Budget Management: Approaches for Enhancement - Meliboev Akhrorjon Anvarjonovich (European Science Publishing, 2024)
The article explores various approaches aimed at enhancing the efficiency, transparency, and accountability of local budget management systems. By analysing current practices and challenges, it identifies key strategies for refining these systems, including the implementation of modern technology, capacity-building initiatives, and stakeholder engagement processes. Through these approaches, the article aims to optimize resource allocation, promote fiscal responsibility, and ultimately contribute to the socioeconomic development of communities. This research provides valuable insights and practical recommendations for policymakers, administrators, and stakeholders seeking to refine and enhance local budget management practices.
Keywords: Local Budget Management, Enhancement, Refinement, Efficiency, Transparency, Accountability, Strategic Approaches, Modern Technology, Capacity Building, Stakeholder Engagement, Resource Allocation, Fiscal Responsibility, Socioeconomic Development, Policy Recommendations, Governance.